Exploring Antibiotic Resistance Diversity in Leuconostoc spp. by a Genome-Based Approach: Focus on the lsaA Gene - Elisa Salvetti; Ilenia Campedelli; Ilaria Larini; Giada Conedera; Sandra Torriani (Microorganisms, 2021)
Leuconostoc spp. are environmental microorganisms commonly associated with fermented foods. Absence of antibiotic resistance (AR) in bacteria is a critical issue for global food safety. Herein, we updated the occurrence of AR genes in the Leuconostoc genus through in silico analyses of the genomes of 17 type strains. A total of 131 putative AR traits associated with the main clinically relevant antibiotics were detected. We found, for the first time, the lsaA gene in L. fallax ATCC 700006T and L. pseudomesenteroides NCDO 768T. Their amino acid sequences displayed high similarities (59.07% and 52.21%) with LsaA of Enterococcusfaecalis V583, involved in clindamycin (CLI) and quinupristin-dalfopristin (QUD) resistance. This trait has different distribution patterns in Leuconostoc nontype strains—i.e., L. pseudomesenteroides, L. lactis and L. falkenbergense isolates from fermented vegetables, cheeses, and starters. To better explore the role of lsaA, MIC for CLI and QUD were assessed in ATCC 700006T and NCDO 768T; both strains were resistant towards CLI, potentially linking lsaA to their resistant phenotype. Contrarily, NCDO 768T was sensitive towards QUD; however, expression of lsaA increased in presence of this antibiotic, indicating an active involvement of this trait and thus suggesting a revision of the QUD thresholds for this species.